Ground beef from electrically stimulated and pre-rigor processed carcasses - Melvin C. Hunt; J.L.A. Kendall; Donald H. Kropf; Michael E. Dikeman; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1980)
Ground beef from electrically stimulated and/or pre-rigor processed carcasses was equivalent to conventional ground beef in texture, palatability, and frozen storage stability, but lost more juice when vacuum-stored, had 2% more total cooking losses from patties, and 1 day less shelf life during display.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Electrical stimulation; Pre-rigor; Carcass